Modern cast iron : the complete guide to selecting, seasoning, cooking, and more - Jones, Ashley L. (Red Lightning Books, 2020)
In Modern Cast Iron, self-proclaimed cast-iron connoisseur Ashley L. Jones recaptures the ease and joy of cooking with cast-iron cookware. Jones introduces readers to the best brands and types of cast-iron cookware to fulfill any cook's needs. She offers detailed tips and tricks for rescuing old, rusted pans and keeping them properly seasoned, and she shares recommendations for the best cooking oil for every recipe. With Jones's help, both experienced and beginner cooks will be able to rival grandma's cooking. Chock-full of stories from Jones's own childhood growing up with cast-iron meals, as well as recipe after tantalizing recipe<U+2015>from breakfast quiche to gluten-free meals and beautiful blueberry cobbler<U+2015>Modern Cast Iron explores the countless ways that cast iron benefits health and happiness.